Web-Based Monitoring Information System for Official Travel Letters on Food Security and North Sumatera Horticulture - Rafli Bima Sakti; Rakhmat Kurniawan (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
The Food Security and Horticulture Office of North Sumatra faces challenges in the management of Service Travel Letters (SPD), such as submitting letters, making letter notes, operational costs, which are still done manually using manual methods, so it is time consuming. This hampers the effectiveness of document management and data-based decision making. To overcome these problems, this research develops a web-based monitoring information system. This system is designed to manage official travel letters, to minimize the time and recording of letter reports. With the web-based Monitoring Information System, the management of official travel letters becomes more structured and can be accessed in real-time, thus increasing efficiency in carrying out official duties in various regions of North Sumatra. This research uses the Research and Development (R&D) method with stages including needs analysis, system design, prototype development, testing, and evaluation. The results of the system implementation show that the use of this Monitoring Information System is able to speed up the process of submitting and approving official travel letters, as well as reducing errors in data collection and recording of trips.